Theoretical foundation of the regulations for investing zakat funds - Ghouini, Samir; Zitout, Ahmed; Abderrazzak, Bouaita (International journal of economic perspectives, 2024)
Zakat funds are an important financial resource for individuals, institutions, and countries. To maximize the benefits from this resource, many countries, such as Algeria, Jordan, Malaysia, and Sudan, have invested these funds in various ways and methods. This study outlines how these funds are invested and presents some practical experiences from a group of countries. It also examines the legal rulings regarding the investment of these funds by presenting the opinions of those who permit and those who prohibit it, as well as highlighting the prevailing view based on legal evidence. Additionally, it specifies the legal controls that govern the investment of zakat funds.